Too Little Oxygen: Ventilation, Prone Positioning, and Extracorporeal Membrane Oxygenation for Severe Hypoxemia - Park, Pauline K. (Seminars in Respiratory and Critical Care Medicine, 2016)
Severe hypoxemia is associated with untoward outcomes in acute respiratory distress syndrome patients. Nevertheless, in and of itself, correction of hypoxemia is not an adequate surrogate outcome for mortality and clear evidence-based targets for correction of hypoxemia remain to be determined. At present, clinical management is directed toward achieving sufficient oxygenation while minimizing toxicity of ventilator-induced lung injury. The gold standard remains lung-protective mechanical ventilation, using lower-tidal volumes and pressure-limited ventilator titration. Notable progress in care includes further refinements in mechanical ventilation, consideration of salutatory effects of early prone positioning and neuromuscular blockade, and exploration of adjunctive extrapulmonary support with extracorporeal membrane oxygenation. This review focuses on three specific aspects: the evolving trend toward open lung ventilation, tempered by the recent cautionary experience with high-frequency oscillation ventilation; the evolution of prone positioning as a treatment for the most hypoxemic patients; and the continued future promise of extracorporeal support as a true rescue therapy.
Keywords: hypoxemia; ARDS; mechanical ventilation; HFOV; open lung ventilation; mechanical ventilation; ECMO